Australia and the World A Festschrift for Neville Meaney. - Beaumont, Joan (Sydney University Press, 2013)
Australia and the World celebrates the pioneering role of Neville Meaney in the formation and development of foreign relations history in Australia and his profound influence on its study, teaching and application.